Is mandatory elective single embryo transfer ethically justified - Tremellen, K; Wilkinson, D; Savulescu, J (Elsevier, 2016)
In-vitro fertilisation (IVF) is an effective form of fertility treatment that is acknowledged to be associated with a higher rate of obstetric complications and poorer neonatal outcomes compared to natural conception. While some of this increased obstetric risk is intrinsic to the infertile population being treated, the practice of multiple embryo transfer and resultant higher order pregnancy also plays a significant role. As a result, several jurisdictions (Sweden, Belgium, Turkey, and Quebec) have moved to legally mandate elective single embryo transfer (eSET) for young women, while other countries such as Australia and New Zealand have effectively mandated eSET by making it a professional industry standard. However, in the United States the ASRM guidelines merely suggest offering eSET to young favourable prognosis patients, and as a result double embryo transfer (DET) is still the norm, with eSET occurring in only 12.2% of cases. In this paper we outline the financial and social advantages of a flexible approach that allows for DET, while also mounting an argument that mandated eSET is an unethical breach of patient autonomy, with an unclear net benefit. Finally, we highlight the inconsistency of banning DET in young women, while still allowing the practice of ovulation induction and intra-uterine insemination-ovulation induction (IUI-OI), two widely used treatments that also pose a significant risk of multiple pregnancies and resultant poor obstetric outcomes.